Prevalence of Reasons for Tooth Extraction in Small- and Medium-Breed Dogs - Chun-Geun Kim; Daehyun Kwon; Kyuyoung Lee; Se Eun Kim; Hyun Min Jo (Animals)
As the life span of companion animals increases and their owners’ concern for their quality of life increases, interest in dental diseases has also gained attention. While many studies have explored oral diseases in general, research on small-breed dogs remains limited. Therefore, in this study, we analyzed various diseases that led to tooth extraction in small- and medium-breed dogs. A study involving 2201 client-owned small- and medium-breed dogs was conducted. All dogs were categorized by sex, age, breed, and tooth position. Teeth were classified into untreated, missing, or extracted categories. For extracted teeth, 14 causes were identified. The results revealed that periodontal disease was the primary cause of tooth extractions, particularly in older dogs and small breeds. In addition to periodontal disease, various other diseases that led to tooth extraction were identified. For these other diseases, the number of extracted teeth increased with age, and brachycephalic breeds exhibited higher extraction rates. The study emphasizes the need for personalized oral care and further research into other contributing factors such as diet and genetics to better understand and manage oral health in dogs. It also offers valuable insights into the broader patterns of tooth extraction associated with various dental diseases.